Analysis Of Teacher Performance Assessed From The Aspects Of Organizational Culture, Motivation, And Competence - Silalahi, Marto; Simatupang, Sudung; Romy, Elly; Candra, Vivi; Sudirman, Acai (Journal of Education Research and Evaluation, 2021)
To support the optimal implementation of education, every educational institution, including schools, strives to improve the performance of their teachers. The stimulus that can be given to make this happen can be in the form of implementing organizational culture, providing motivation, and increasing competence. The substance of this study is to determine the effect of organizational culture, motivation, and competence on teacher performance. The sample in this study amounted to 215 respondents who were determined by the purposive sampling approach. Data analysis using the SPSS application by displaying the results of data processing through test research instruments with validity and reliability, multiple regression analysis, the coefficient of determination, and hypothesis testing. The research results prove that all the hypotheses developed in this study are acceptable. The first hypothesis shows that organizational culture has a significant effect on teacher performance. The second hypothesis shows that motivation has a significant effect on teacher performance. Furthermore, the third hypothesis shows that competence has a significant effect on teacher performance.